Orientasi Rigid dan Moderat dalam Penafsiran Original Intent dan Praktiknya di Indonesia - Muhammad Alwi Khoiri Ramdani; Susi Dwi Harijanti; Lailani Sungkar (Jurnal Konstitusi)
An original intent is an approach to interpreting the Constitution that seeks to reveal the meaning according to the intent of the drafters. In practice, this method contains problems, the interpretation by the Constitutional Court produces different meanings and develops even though it is based on the same method. It is necessary to carry out an analysis of the development of thought in the application of the original intent method as well as an analysis of the pattern application of the original intent in the constitutional interpretation in Indonesia. This is normative/doctrinal research. The results of the study indicate that there is a development of thought in the application of the original intent method which is oriented towards being rigid and moderate. The Court tends to apply the original intent to (1) the mechanism for filing state institutions/officials; (2) the authority of state institutions; and (3) human rights.